Histopathological features of endometrium in those with symptoms suggestive of female genital tuberculosis - R., Sankareswari; S., Arthy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Genital tuberculosis is an important cause of female infertility. It is estimated that 5-13 percent of females presenting themselves in infertility clinics in India have genital tuberculosis. Objective of present study was to compare the prevalence of symptoms suggestive of genital tuberculosis between the patients suffering from infertility and the patients with normal fertility. Methods: A random of 200 female OPD patients who were proved to be negative for genital TB (FGTB) by Microscopy, AFB culture, AFB-PCR and histopathology were retrospectively analyzed for presence of symptoms suggestive of FGTB. A comparative study was done to find any specific association of symptoms suggestive of FGTB with infertility. Results: Oligomenorrhoea was the only symptom significantly (p=0.02) associated with those suffering from infertility [n= 64 (32%)]. The rest of the symptoms suggestive of FGTB were not significantly associated with infertility. Conclusions: Symptoms suggestive of FGTB are present even in those who are proved Negative for FGTB and non-significantly associated with those with infertility in whom FGTB is expected to be an important cause. This paradox questions the specificity of these symptoms in developing a symptomatic diagnostic algorithm for FGTB.